Effect of heat treatment on the mechanical properties of 3D-printed polyamide 12 composites - Choo, Jasper Yeng Chee (Nanyang Technological University, 2021)
Multi-jet fusion (MJF), which was developed by HP, is a relatively new AM method compared to selective laser sintering (SLS) that has been around for quite some time. MJF displays great potential in producing quality, functional parts. Both MJF and SLS falls under the same category of AM. The main difference between SLS and MJF is the heat source and the additional agents used in MJF. This allows MJF to produce the same part as SLS within a shorter period of time. In this project, the effect of annealing temperatures and durations on the mechanical properties of MJF-printed PA12 and GF/PA12 composites were investigate. Different weight fractions of glass fibres (GF) reinforcements, ranging from 0 wt% to 30 wt% were mixed into the polyamide-12 (PA12) matrix powder. It was found that high-temperature annealing can significantly enhance the mechanical strength of MJF-printed PA12 and GF/PA12 specimens. Results showed that build orientation would affect the mechanical properties of printed specimens due to fibre orientation. Annealing temperature was found to have a higher contributing factor as compared to the annealing duration. At 20 wt% GF, GF/PA12 specimens had a tensile strength of 59.35 MPa (improved by 27.6%) and a tensile modulus of 5.25 GPa (improved by 222.1%) after high-temperature annealing. However, there was a significant decrease in strain. The increase in mechanical properties was a result of an increase in crystallinity. The heat treatment process was also found to increase the melting temperature of MJF-printed specimens by more than 4 °C.